2021
DOI: 10.3390/bios11120489
|View full text |Cite
|
Sign up to set email alerts
|

A Pencil-Lead Immunosensor for the Rapid Electrochemical Measurement of Anti-Diphtheria Toxin Antibodies

Abstract: Diphtheria is a vaccine-preventable disease, yet immunization can wane over time to non-protective levels. We have developed a low-cost, miniaturized electroanalytical biosensor to quantify anti-diphtheria toxin (DTx) immunoglobulin G (anti-DTx IgG) antibody to minimize the risk for localized outbreaks. Two epitopes specific to DTx and recognized by antibodies generated post-vaccination were selected to create a bi-epitope peptide, biEP, by synthesizing the epitopes in tandem. The biEP peptide was conjugated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 58 publications
(81 reference statements)
0
9
0
2
Order By: Relevance
“…First, the one-way ANOVA test was performed with a significance of 95% to check whether the device-to-device surface variation during the optimization of preparation or analytical parameters -e.g., sequence of EP, sec-IgG and EP concentrations, and serum dilution ratio -was significant, as done in studies found in the literature [7,17,18]. Next, a two-tailed Students t-test with a confidence level of 95% was performed for pairwise comparisons [7,17,18].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…First, the one-way ANOVA test was performed with a significance of 95% to check whether the device-to-device surface variation during the optimization of preparation or analytical parameters -e.g., sequence of EP, sec-IgG and EP concentrations, and serum dilution ratio -was significant, as done in studies found in the literature [7,17,18]. Next, a two-tailed Students t-test with a confidence level of 95% was performed for pairwise comparisons [7,17,18].…”
Section: Discussionmentioning
confidence: 98%
“…Serological diagnostic tests that utilize the presence of antibody as the definition for if an individual was infected by a pathogen detects antibodies in their serum or blood. This can be conducted as a lab-based assay such as an enzyme-linked immunosorbent assay (ELISA) [7] or chemiluminescent immunoassay [22], which are time-consuming and expensive, or a point-of-care test based on lateral flow technology that can show limited sensitivity [23,24]. We propose to implement an electrochemical assay based on commercially available SPEs that can be easily sensitized to capture diagnostic antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations